Parties prenantes VBDC Stakeholders - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2012)
Some questions: How is your project linked to each of these stakeholders? What is a “boundary partner”? How do you define “end user” and “next user”? Where are the bi-lateral organizations, e.g. DANIDA? How is your project linked your end/next users’ partners? How do these links affect your relationship with your end/next users? Do the stakeholder groupings and their colors make sense?